Faculty Perceptions of Student Recruitment and Retention in STEM Fields - MaryKay Orgill; Heather Skaza; Erica Marti; PG Schrader; Eshani Gandhi-Lee (Lectito Journals, 2017)
According to the President's Council of Advisors on Science and Technology (PCAST, 2012), there is a need to produce one million more STEM (Science, Technology, Engineering, and Mathematics) graduates in the U.S. over the next decade. Thus, more students must be recruited into and retained in STEM degrees of study. Because faculty are considered influential in students' choices to pursue and remain in STEM disciplines, we interviewed university STEM faculty in order to identify their perceptions of student recruitment and retention in STEM fields. Our data indicate that faculty are generally unaware of or not worried about the need to produce additional STEM graduates. Additionally, faculty seem to be unaware of the actions they might take to positively influence STEM recruitment and retention at the post-secondary level. Here, we specifically discuss faculty perceptions of (1) the gap between the number of STEM graduates and the number of STEM workers available for STEM-related jobs, (2) why students may not be going into or remaining in STEM fields, and (3) their own roles in recruiting and retaining students in STEM fields.